Development and Prospective Federal State-Wide Evaluation of a Device for Height-Based Dose Recommendations in Prehospital Pediatric Emergencies: A Simple Tool to Prevent Most Severe Drug Errors. (4th March 2018) - Kaufmann, Jost; Roth, Bernhard; Engelhardt, Thomas; Lechleuthner, Alex; Laschat, Michael; Hadamitzky, Christoph; Wappler, Frank; Hellmich, Martin
Abstract: Objective : Drug dosing errors pose a particular threat to children in prehospital emergency care. With the Pediatric emergency ruler (PaedER), we developed a simple height-based dose recommendation system and evaluated its effectiveness in a pre–post interventional trial as the Ethics Committee disapproved randomization due to the expected positive effect of the PaedER on outcome. Methods : Pre-interventional data were retrospectively retrieved from the electronic records and medical protocols of the Cologne Emergency Medical Service over a two-year period prior to the introduction of the PaedER. Post-interventional data were collected prospectively over a six-year period in a federal state-wide open trial. The administered doses of either intravenous or intraosseous fentanyl, midazolam, ketamine or epinephrine were recorded. Primary outcome measure was the number and severity of drug dose deviation from recommended dose (DRD) based on the patient's weight. Results : Fifty-nine pre-interventional and 91 post-interventional prehospital drug administrations in children were analyzed. The rate of DRD > 300% overall medications were 22.0% in the pre- and 2.2% in the post-interventional group (p < 0.001). All administrations of epinephrine occurred excessive (DRD > 300%) in pre-interventional and none in post-interventional patients (p < 0.001). Conclusions : The use of the PaedER resulted in a 90% reduction of medication errors (95% CI: 57% to 98%; p < 0.001) and prevented all potentially life-threatening errors associated with epinephrine administration. There is an urgent need to increase the safety of emergency drug dosing in children during emergencies. A simple height-based system can support health care providers and helps to avoid life-threatening medication errors.